Shoulder pain as one of the symptoms of syringomyelia - Ślusarz, Krystian; Wierzbicki, Krzysztof; Adamczyk-Sowa, Monika (Journal of Education, Health and Sport, 2019)
Syringomyelia is typically a progressive chronic condition caused by a disruption of normal cerebrospinal fluid flow. Earlier diagnosis is associated with better outcomes, because although the progression of neurological deficits usually stabilizes after intervention, many patients still remain at least partially symptomatic.In this paper, we describe the case of a 33-year-old female patient with syringomyelia. The patient reported to the Department of Neurology due to sensory disorders and shoulder pain for several months. On admission, neurological examination revealed right hand muscular deficit, abolition of sensation of temperature and asymmetry of tendon reflexes. A few weeks earlier, outpatient magnetic resonance imaging (MRI) of the cervical spine showed the features of Arnold-Chiari malformation, syringomyelia and C5/C6 and C6/C7 discopathy. During hospitalization, MRI of the thoracic spine was performed, and the syringomyelic cavity C2–Th6 was revealed. The patient in stable condition was discharged home and referred to the neurosurgery department. The patient underwent a medial sub-occipital craniectomy and, a month later, was admitted to the neurological rehabilitation department due to paresis and sensory disturbances of right upper limb. As a result of the physiotherapy, the right arm's motor function and general physical condition improved.